Self‐Healing Properties of Alkali Metals under "High‐Energy Conditions" in Batteries. Issue 21 (22nd April 2021) - Li, Yuqian; Zhang, Liyuan; Zhang, Jiaheng; Wang, Xiuli; Gu, Changdong; Xia, Xinhui; Tu, Jiangping
Abstract: With the development of high‐energy‐density metal batteries, dendrite growth has become a bottleneck for the further improvement of alkali metal electrodes. In this study, the self‐healing performance of dendrites under "high‐energy conditions" are predicted and verified. Initially, the driving force of self‐healing is analyzed based on surface energy. Theoretically, the activation energy for atom diffusion, which contributes to the resistance of self‐healing, is quantitatively calculated. Moreover, to illustrate self‐healing in Li, Na, and K electrodes, electrochemical curves, in situ optical images, and SEM images are obtained at different temperatures and current densities. Based on the results, it is concluded that K dendrites under "high‐energy conditions" (i.e., at high temperatures and high current densities) possess the highest self‐healing ability and reparability. Consequently, the self‐healing properties of alkali metals under high‐energy conditions are theoretically and experimentally examined and confirmed. Abstract : Dendrites have a driving force for self‐healing due to their high specific surface area. In this paper, the self‐healing properties in the alkali metal batteries are analyzed, and observed at distinct temperatures and current densities. The "high‐energy condition" promotes the reparability of metal electrodes.